The Relation Between Temperature and Time on the Application of Coconut Fiber Cement Panels as Potential for Wall Cover - Kemala Jeumpa (Jurnal Inovasi Teknologi, 2022)
This research is about coconut fiber material which has the potential to wall cover and the relationship between temperature and time of coconut fiber material in reducing temperature. The wall, as one of the building envelopes, endures high sun radiation. It needs the wall material that can reduce temperature to ensure thermal comfort inside the building. Gaining building thermal comfort requires architecture, knowledge, and skills as well as innovation. Lowering temperature in the room can be done through wall modifications so that it can lessen the use of air-con. Thus, research on the use of natural materials such as coconut fiber for walls is needed. This study is using an experimental approach. The coconut fiber was tested to measure the temperature reduction and study its linear equations from the relation between temperature and time given. The analysis is comparing two materials: (1) the mix of cement and sand without coconut fiber; (2) The mix of cement and coconut fiber material. The testsâ€™ procedures are applying heat temperature to the side of the material and measuring the resulting absorbed temperature on the other side of both materials. Both of the material were exposed to 35Â°C heat temperature for 150 minutes. The materials are set in a box. The tests use 3 thermal sensors are T1, T2 and T3 and one heater. This heater is connected to the power source and a device to control the temperature given called Ts controller. The test shows different results between the temperature of material with coconut fiber and material without coconut fiber. The coconut fiber material has a lower temperature than that of without coconut fiber. The linear equation of the coconut fiber material related to the time and temperature shows the longer time, the lower the temperature is. Thus, it indicates the potential of coconut fiber material used as cover for building walls.